Experimental Study and Numerical Analysis of Crane Operability in Floating Crane Catamaran - Rizky Arrico Farhan; Eko Budi Djatmiko; Murdjito Murdjito; Abdul Ghofur (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2021)
Crane vessel is a floating structure equipped with accommodation facilities and one or more cranes to do work in the field. Crane vessel continue to be developed so that they can lift large structures and operate safely in certain environmental conditions. The work that is usually done by crane vessel is to lift heavy or light loads from land to ship, from ship to land, from ship to sea, from sea to ship, and from ship to ship. The process of moving loads carried out by a crane vessel usually called the lifting process. In carrying out its work, a crane vessel is limited by certain criteria for safety reasons. One of them is the criterion that limits the heave motion at the end of the crane boom and roll and pitch motion of the crane vessel. In this final project, an experimental study and numerical analysis of crane operability were carried out on catamaran hulled crane vessel. Experiments were carried out at the Balai Teknologi Hidrodinamika BPPT and numerical analysis using the MOSES software. According to the criteria used, namely Operational Limitations of Offshore Crane Vessels, cranes on floating crane catamaran have the highest operability when the vessel heading is 0o to the direction of the incoming waves, which is up to Hs 1.45 m.